Sort of super - Gapstur, Eric (Aladdin, 2022)
"Eleven-year-old Wyatt Flynn had something amazing happen to him: he got superpowers! Good ones too, like super-flight, super-strength, and super-speed. The only problem? Wyatt got his superpowers totally by mistake, and his dad--who's been overprotective since Wyatt's mom disappeared--thinks he's too young for them and worries what would happen if everyone found out. So he makes Wyatt hide his powers. Keeping such a huge secret from his best friends Beto and Nara is bad enough, but not being able to use his new abilities to defend them from the biggest bully at school makes Wyatt feel useless and frustrated. But his little sister thinks the good his powers could do is more important than following Dad's rules. Slowly, the two of them become a dynamic crime-fighting duo right under their dad's nose. Lying to his dad isn't much easier than lying to his friends. But Wyatt might be able to make a real difference in the community ... and maybe even find Mom. That makes it all worth it--right?"--